Fig. 3 in Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic ... - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Fig. 3. Stylodes and digitiform extensions on parapodia of Sthenelais boa (Johnston, 1833), ventral view (photograph by D. Fiege, Senckenberg Museum). Scale bar: 250 µm. ... : Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on page 151, DOI: 10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646 ...